THE TEACHER’S ROLE IN HANDLING BULLYING BEHAVIOR IN FOURTH GRADE ELEMENTARY SCHOOL STUDENTS - Frida Wahyu Rahmawati; Almuntaqo Zainuddin (Jurnal Cakrawala Pendas, 2023)
Bullying behavior is carried out consciously to hurt others mentally and physically. Bullying behavior is also often done by students at school, including fourth grade students at SDN Tunggulsari 1. Therefore, the teacher’s role is needed in overcoming and reducing bullying. This research was conducted to find out the forms of bullying behavior, the teacher's role in dealing with bullying behavior, and the obstacles experienced by the teacher during the process. The research conducted is included in the type of descriptive qualitative research with a case study approach model. The informants in this study were school principals, fourth grade teachers, bullies and victims of bullying. This study uses the data analysis technique of the Miles & Huberman model which is carried out in three stages including data reduction, analysis and presentation of data, drawing conclusions. Data collection techniques with direct field observations, in-depth interviews, and documentation. Teachers and schools have handled student bullying behavior quite well. The results of the study show that teachers play a significant role in dealing with bullying in the classroom. Several ways are carried out to overcome and reduce bullying behavior. The role of the teacher in preventing bullying is carried out in several ways including socializing bullying to students, being assertive about deviant actions, instilling harmony and respect for others, forming study groups, instilling religious values, and establishing harmonious relations with students. Then the teacher's role in overcoming bullying was found as gathering information, reconciling students, providing counseling, providing emotional support, and taking follow-up actions. The results of this study can be used as a reference for the development of appropriate and effective bullying prevention efforts by various parties, especially teachers in schools. Perilaku bullying merupakan suatu tindakan yang dilakukan secara sadar untuk menyakiti orang lain secara mental maupun fisik. Perilaku bullying juga masih sering dilakukan para siswa di sekolah, termasuk siswa kelas 4 di SDN Tunggulsari 1. Oleh karenanya, peran guru sangatlah diperlukan dalam mengatasi dan mengurangi adanya tindakan bullying. Penelitian ini dilakukan untuk mengetahui bentuk-bentuk perilaku bullying, peran guru dalam menangani perilaku bullying, dan hambatan yang dialami guru selama prosesnya. Penelitian yang dilakukan termasuk ke dalam jenis penelitian kualitatif deskriptif dengan model pendekatan studi kasus. Narasumber dalam penelitian ini adalah kepala sekolah, guru kelas empat, pelaku bullying dan korban bullying. Penelitian ini menggunakan teknik analisis data model Miles & Huberman yang dilakukan dalam tiga tahap meliputi reduksi data, analisis dan penyajian data, penarikan kesimpulan. Teknik pengumpulan data dengan observasi lapangan secara langsung, wawancara secara mendalam, dan dokumentasi. Guru dan sekolah telah melakukan penanganan terhadap perilaku bullying siswa dengan cukup baik. Hasil penelitian menunjukkan bahwa guru berperan besar dalam menangani adanya tindakan bullying di kelas. Berbagai cara dilakukan untuk dapat mengatasi dan mengurangi perilaku bullying yang terjadi. Peran guru dalam pencegahan bullying dilakukan dengan berbagai cara meliputi sosialisasi bullying kepada para siswa, bersikap tegas terhadap tindakan menyimpang, menanamkan sikap rukun dan menghargai sesama, membentuk kelompok belajar, menenamkan nilai religious, serta menjalin hubungan harmonis dengan siswa. Kemudian peran guru dalam mengatasi bullying yang ditemukan seperti mengumpulkan informasi, mendamaikan siswa, memberikan konseling, memberikan dukungan emosional, dan melakukan tindakan lanjutan. Hasil penelitian ini dapat dijadikan acuan pengembangan upaya pencegahan bullying yang tepat dan efektif oleh berbagai pihak khususnya guru di sekolah.